2013
DOI: 10.1111/asj.12159
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biological networks and biological pathways associated with residual feed intake in beef cattle

Abstract: In this study, biological networks were reconstructed from genes and metabolites significantly associated with residual feed intake (RFI) in beef cattle. The networks were then used to identify biological pathways associated with RFI. RFI is a measure of feed efficiency, which is independent of body size and growth; therefore selection for RFI is expected to result in cattle that consume less feed without adverse effects on growth rate and mature size. Although several studies have identified genes associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 44 publications
8
44
0
Order By: Relevance
“…Moreover, some of the significantly enriched GO terms were associated with fat metabolisms, such as monocarboxylic acid and oxyacid metabolic processes. Interestingly, it has been shown that there is a relationship between lipid metabolism and feed efficiency (Nafikov and Beitz 2007;Karisa et al 2014). For example, by increasing the fat sources in a broiler diet, the FI amount is decreased and feed efficiency is improved (Firman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of the significantly enriched GO terms were associated with fat metabolisms, such as monocarboxylic acid and oxyacid metabolic processes. Interestingly, it has been shown that there is a relationship between lipid metabolism and feed efficiency (Nafikov and Beitz 2007;Karisa et al 2014). For example, by increasing the fat sources in a broiler diet, the FI amount is decreased and feed efficiency is improved (Firman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminant production, especially beef cattle operation, is important for the production of high-quality animal protein (meat). Feed efficiency is one of the most important traits in beef cattle production because the feed cost accounts for approximately 60-70% of the total production cost (Karisa et al, 2014). Therefore, improving feed efficiency in beef cattle can maximize the production efficiency when lower or the same amount of feed is consumed by cattle under current management conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple studies have reported that the rumen microbial composition is associated with feed efficiency in beef (5-9) and dairy (10) cattle, suggesting that rumen microbial function is one of the factors that impact the cattle's feed efficiency. Feed efficiency is one of the most important traits in cattle farming because the feed cost accounts for most of the production expense, accounting for 60 to 70% of the total cost in beef production (11). In addition, efficient beef cattle produce 20% less methane than inefficient ones (12); hence, enhancing the feed efficiency of beef cattle can also decrease their environmental footprint.…”
mentioning
confidence: 99%